Beyond Law 180 (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Law 180 was a “demiurgic” law, but today it appears to be in great difficulty and at risk of regressing by showing obvious regressive phenomena. Certainly, a law of rupture, but also an unfinished reform process that, due mainly to the persistence of old ideologies/apologies, cannot really move forward and consequently overcome its undeniable financial and organizational problems. The progressive nature of Law 180 has so far been denied. The idea of a one-time law has been asserted. Such denial, however, risks, relative to the major problems of social legitimacy, that the entire sector will pay a very high price in credibility.
Keywords: Law 180; regressivity; apologia; reform; credibility